2014
DOI: 10.1051/0004-6361/201423451
|View full text |Cite
|
Sign up to set email alerts
|

Clustering, host halos, and environment ofz ~ 2 galaxies as a function of their physical properties

Abstract: Using a sample of 25 683 star-forming and 2821 passive galaxies at z ∼ 2, selected in the COSMOS field following the BzK color criterion, we study the hosting halo mass and environment of galaxies as a function of their physical properties. Spitzer and Herschel allow us to obtain accurate star formation rate estimates for starburst galaxies. We measure the autocorrelation and cross-correlation functions of various galaxy subsamples and infer the properties of their hosting halos using both a halo occupation mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
54
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 90 publications
20
54
1
Order By: Relevance
“…The ACFs show that the dropout galaxies are more strongly clustered with higher stellar mass thresholds. This trend is also seen in previous clustering studies with stellar-mass limit samples at lower-z (e.g., Béthermin et al 2014;McCracken et al 2015).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The ACFs show that the dropout galaxies are more strongly clustered with higher stellar mass thresholds. This trend is also seen in previous clustering studies with stellar-mass limit samples at lower-z (e.g., Béthermin et al 2014;McCracken et al 2015).…”
Section: Resultssupporting
confidence: 85%
“…The HOD model was developed to interpret galaxy clustering by characterizing the number of galaxies within dark haloes as probability distributions, assuming that galaxy baryonic properties are primarily governed by the masses of their host dark haloes. Many observational studies have successfully unveiled the relationship between observed galaxies and their host dark haloes for high-redshift Universe (e.g., Geach et al 2012;Béthermin et al 2014;Durkalec et al 2015;Harikane et al 2016;Ishikawa et al 2016;Park et al 2016), as well as z < 1 Universe (e.g., Zehavi et al 2011;Matsuoka et al 2011;Coupon et al 2012Coupon et al , 2015Rodríguez-Torres et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…in Hartley et al (2013), Sato et al (2014), McCracken et al (2015, and Lin et al (2016), but contrary to what was reported in Béthermin et al (2014). This finding implies that halo mass could play a major role in quenching the star formation, in line with theoretical models that advocate the halo quenching scenario (e.g., Cen 2011).…”
Section: Halo Quenchingsupporting
confidence: 70%
“…In Figure 1 we show the location of our z∼3.2 sample in the SFR versus  M plane with respect to the location of the "MS" of star-forming galaxies at redshift » z 3 (Lee et al 2010;Magdis et al 2010;Bethermin et al 2014;Heinis et al 2014;Schreiber et al 2015;Tasca et al 2015;Tomczak et al 2016). 13 Our ALMA detections sample the MS at high stellar mass ( ( [ ]) -…”
Section: Stellar Mass and Sfr Estimationmentioning
confidence: 99%
“…AGNs are highlighted in red (see the text for details). 13 In the compilation of MSs used by the 2-SFM framework (Sargent et al 2014) and updated with recent sSFR measurements (Bethermin et al 2014;Heinis et al 2014;Steinhardt et al 2014;Schreiber et al 2015;Tasca et al 2015), galaxies with stellar masses of…”
Section: Ghz Continuum Detection and Gas Mass Measurementsmentioning
confidence: 99%